Rule Technologies: Foundations, Tools, and Applications 9th International Symposium, RuleML 2015, Berlin, Germany, August 2-5, 2015, Proceedings - Bassiliades, Nick; Gottlob, Georg; Sadri, Fariba; Paschke, Adrian; Roman, Dumitru (Programming and Software Engineering,, 2015)
This book constitutes the refereed proceedings of the 9th International RuleML Symposium, RuleML 2015, held in Berlin, Germany, in August 2015. The 25 full papers, 4 short papers, 2 full keynote papers, 2 invited research track overview papers, 1 invited paper, 1 invited abstracts presented were carefully reviewed and selected from 63 submissions. The papers cover the following topics: general RuleML track; complex event processing track, existential rules and datalog+/- track; legal rules and reasoning track; rule learning track; industry track.